Clinical Application of iNKT Cell-mediated Anti-tumor Activity Against Lung Cancer and Head and Neck Cancer - Takami, Mariko; Ihara, Fumie; Motohashi, Shinichiro (Frontiers in Immunology, 2018)
Invariant natural killer T (iNKT) cells produce copious amounts of cytokines in response to T-cell receptor (TCR) stimulation by recognizing antigens such as -galactosylceramide (-GalCer) presented on CD1d; thus, orchestrating other immune cells to fight against pathogen infection and tumors. Because of their ability to induce strong anti-tumor responses and the convenience of their invariant TCR activated by a synthetic ligand, -GalCer, iNKT cells have been intensively studied for application in immunotherapeutic approaches to treat cancer patients in the clinic. Here, we summarize the clinical trials of iNKT cell based immunotherapy for non-small cell lung cancer, and head and neck cancer. Although solid tumors are thought to be refractory to immunotherapeutic approaches, our clinical trials showed that the intravenous injection of -GalCer-pulsed antigen presenting cells (APCs) activated endogenous iNKT cells and iNKT cell dependent responses. Moreover, an increase in the number of IFN- producing cells in PBMCs was associated with prolonged survival. The marked infiltration of iNKT cells and the accumulation of conventional T cells in the tumor microenvironment were also observed after the administration of -GalCer-pulsed APCs and/or ex vivo activated iNKT cells. In cases of advanced head and neck squamous cell carcinoma, the increased accumulation of iNKT cells in the tumor microenvironment was correlated with objective clinical responses. We will also discuss potential combination therapies of iNKT cell based immunotherapy to achieve enhanced anti-tumor activity and provide better treatment options for these patients.